Trans-kingdom sRNA silencing in the prevention and control of crop Fusarium wilt disease - Xin-Ni Huang; Yue Wang; Yan-Ting Li; Ying Xiao; Shou-Qiang Ouyang (Phytopathology Research)
Abstract The Fusarium oxysporum species complex (FOSC), comprising a multitude of soil borne fungal pathogens, represent a major group of plant invaders that cause vascular wilt diseases of crops worldwide. Although sexual reproduction is nebulous in the FOSC, horizontal gene transfer (also well known as trans-kingdom) may contribute to the observed diversity in pathogenic strains. Concerning the safety and costly process of generating genetically modified crops, a plant-disease management strategy not reliant on transgenic approaches remains the most economic and environmental-friendly option. Here, we highlight the current scenario via beginning with F. oxysporum formae speciales and races as well as caused Fusarium wilt disease in field. Subsequently, based on the mechanisms by which small RNA (sRNA) acts in gene silencing, especially in bidirectionally trans-kingdom sRNA silencing between F. oxysporum and their hosts in the development of disease, we summarize technological breakthroughs like Spray-Induced Gene Silencing (SIGS) technology in the developing and applying to protect crops from Fusarium wilt disease. Given that SIGS has been developed and recently applied in controlling crop Fusarium wilt diseases, we propose a potential prevention and control system to exploit crop Fusarium-vasculature interaction leading to further study trans-kingdom sRNA silencing.